Diagnostic value of α1-MG and URBP in early diabetic renal impairment - Zhou, Yukun; Zhang, Yiding; Chen, Jiaojiao; Wang, Ting; Li, Huangmin; Wu, Feng; Shang, Jin; Zhao, Zhanzheng (Frontiers in Physiology, 2023)
Diabetic kidney disease (DKD) is defined as diabetes with impaired renal function, elevated urinary albumin excretion, or both. DKD is one of the most common microvascular complications of diabetes and plays an important role in the cause of end-stage renal disease (ESRD).About 5% of people with type 2 diabetes (T2DM) already have kidney damage at the time they are diagnosed, but other triggers of renal insufficiency, such as obesity, hyperlipidemia, glomerular atherosclerosis are often present, making it difficult to define "diabetic kidney disease"or"diabetic nephropathy" precisely in epidemiology or clinical practice.Therefore, the aim of this study is to identify diabetic patients with CKD at an early stage, and evaluate the value of tubular injury markers including α1-MG, β2-MG, NAG)and URBP in the development of diabetes to DKD.Materials and Methods: We recruited a total of 182 hospitalized patients with T2DM in the First Affiliated Hospital of Zhengzhou University from February 2018 to April 2023.Based on their levels of UACR and GFR,patients were divided into DM group (UACR≤30mg/g and eGFR≥90ml/min/1.73m2, n=63) and DKD group (UACR＞30mg/g or eGFR＜90ml/min/1.73m2, n=119) excluding other causes of chronic kidney disease. We further developed diagnostic models to improve the ability to predict the risk of developing DKD by screening potential risk factors using univariate and multivariate logistic regression analysis.Calibration plots and curve analysis were used to validate the model and clinical usefulness. Next, we screened patients with relatively normal estimated glomerular filtration rate (eGFR) (≥90 mL/ min/1.73 m2) to investigate whether tubular injury markers could accurately predict the risk of DKD in patients with normal renal function.We defined the rate of GFR decline as a prognostic indicator of renal function in patients and collected the information of the re-hospitalized DKD patients to determine whether the relevant indicators had an impact on the renal prognosis.Results: The patients with DKD had higher levels of tubular injury markers than patients with DM. URBP, α1-MG, eGFR were statistically different in both univariate and multivariate logistic regression analyses and displayed great predictive power after modeling with an area under curve of 0.989.Conclusions:Tubular injury markers play an important role in early diabetic renal function impairment.